A sex-structured model for the transmission of trichomoniasis with possible reinfection. Issue 2 (3rd April 2021) - Terefe, Yibeltal Adane
ABSTRACT: Trichomoniasis is a sexually transmitted disease caused by an infection from the parasite Trichomonas vaginalis . A model of its transmission shows a backward bifurcation when the basic reproduction number R 0 is less than one. A stable disease-free equilibrium co-exists with a stable endemic equilibrium with the consequence that the disease may invade the population even when R 0 < 1 . The backward bifurcation is due to reinfection among the people who have recovered. In the absence of a backward bifurcation and when R 0 < 1, the disease-free equilibrium has global asymptotic stability. In the absence of reinfection, the model has a unique global asymptotically stable endemic equilibrium when R 0 > 1 . Contact rates are the major parameters in the persistence of the disease, compared to rates of recovery after treatment, infectiousness of asymptomatic individuals, and rates of reinfection.